Performa Entog (Cairina moschata) Jantan Yang Diberi Berbagai Imbangan Pakan Berbasis Silase Limbah Sayuran dan Dedak Padi - Fazar Maulana; Dini Widianingrum; Aaf Falahudin (Tropical Livestock Science Journal, 2023)
Muscovy duck performance is influenced by quality feed, easy to obtain and does not compete with humans. The purpose of this study was to analyze the performance of male mussels fed a balanced feed of vegetable waste and rice bran silage on the performance of male mussels and to obtain a formulation of a balanced diet of vegetable waste and rice bran silage that produced the best mussels performance. The study was conducted experimentally using a completely randomized design (CRD) of 4 treatments with 5 replications. The treatment used was 4 feed balances, namely rice bran with vegetable waste silage, respectively P0 = 100: 0; P1 = 75 : 25; P2 = 50 : 50, and P3 = 25 : 75. The variables observed were ration consumption, body weight gain, ration conversion, and feed efficiency. The research data were analyzed using analysis of variance and if there was a significant difference it was further tested using Duncan's multiple range test. The results showed that ration consumption, ration conversion, and feed efficiency had significant differences. Meanwhile, body weight gain did not have a significant effect. It can be concluded that feeding vegetable waste silage has a significant effect on increasing ration consumption, but reducing ration conversion and feed efficiency. The treatment that produced the best male musk performance was shown at P0.